2008
DOI: 10.1002/bip.21071
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide RP‐1 structure and interactions with anionic versus zwitterionic micelles

Abstract: ABSTRACT:Topologically, platelet factor-4 kinocidins consist of distinct N-terminal extended, C-terminal helical, and interposing g-core structural domains. The C-terminal a-helices autonomously confer direct microbicidal activity, and the synthetic antimicrobial peptide RP-1 is modeled upon these domains. In this study, the structure of RP-1 was assessed using several complementary techniques. The highresolution structure of RP-1 was determined by NMR in anionic sodium dodecyl sulfate (SDS) and zwitterionic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
58
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 65 publications
7
58
0
1
Order By: Relevance
“…The similarity of TRP3 conformations and of some of its analogs stabilized by different micellar interfaces has been indicated by NMR, CD, and fluorescence experiments (13,14,17,29,70). Similar results were found for melittin in micelles of various detergentes (45) and for PR-1, a synthetic peptide modeled after the microbicide domains of the platelet microparticle factor-4 family, in SDS and DPC micelles (71).…”
Section: Conformation Of Trp3 Bound To the Micellar Systemssupporting
confidence: 62%
“…The similarity of TRP3 conformations and of some of its analogs stabilized by different micellar interfaces has been indicated by NMR, CD, and fluorescence experiments (13,14,17,29,70). Similar results were found for melittin in micelles of various detergentes (45) and for PR-1, a synthetic peptide modeled after the microbicide domains of the platelet microparticle factor-4 family, in SDS and DPC micelles (71).…”
Section: Conformation Of Trp3 Bound To the Micellar Systemssupporting
confidence: 62%
“…The synthetic host defense peptide RP-1 is an 18-amino-acid peptide (N-ALYKK 5 -FKKKL 10 -LKSLK 15 -RLG 18 -C; mass, 2,163 Da) modeled in part upon ␣-helical C-terminal microbicidal domains of mammalian CXCL4 kinocidins (5). AA-RP-1 is an anthryl-alanine-substituted (position 2) congener of the parent peptide RP-1.…”
Section: Methodsmentioning
confidence: 99%
“…AA-RP-1 is an anthryl-alanine-substituted (position 2) congener of the parent peptide RP-1. Peptides were synthesized with a Symphony multiplex synthesizer (Rainin, Woburn, MA) and authenticated by mass spectroscopy and amino acid analysis (5,46). Purified peptides were lyophilized and resuspended in sterile phosphate-buffered saline (PBS) for use in the assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed structure-function studies have shown that positively charged residues on the surface of these chemokines, especially at their C-terminal ␣-helices, are largely responsible for their direct antimicrobial activity (4,9,28,39,56,63). Peptides of the ␣-helical portions of some chemokines have been shown to have preferential interactions with anionic lipids over zwitterionic lipids (5,6), and the full chemokines are believed to act by perturbing bacterial membranes similarly to antimicrobial peptides (10,17).…”
mentioning
confidence: 99%